SKRINING FITOKIMIA EKSTRAK ETANOL DAN FRAKSI-FRAKSI DAUN ALAMANDA (Allamanda Catharica L.) - Nur Jannah (PROSIDING SEMINAR KIMIA, 2020)
The utilization of Alamanda leaf phytochemical test is an important step in the effort to reveal the potential resources of medicinal plants. The purpose of this research was to determine the secondary metabolite compounds contained in Alamanda leaves. The process is carried out through a preparation process, namely the process of cleaning and drying the sample using room temperature for 1 month and obtaining 180 grams of Alamanda leaf samples. The maceration process, namely the process of soaking the sample using 96% ethanol as a solvent, was carried out for 2 x 24 hours after which the rotary evaporator was carried out and obtained 6 grams of total ethanol extract. The fractionation process using n-hexane, ethyl acetate and residual ethanol solvents was carried out based on differences in polarity and weight in each fraction. The results of the n-hexane fraction, ethyl acetate fraction and residual ethanol fraction were 2; 2 and 1 gram. The phytochemical test was carried out on the total ethanol extract, n-hexane fraction, ethyl acetate fraction and residual ethanol fraction. The results obtained from the phytochemical test were that the total ethanol extract contained alkaloids, triterpenoids, flavonoids and phenolics. The n-hexane fraction contains alkaloids, triterpenoids and flavonoids. The ethyl acetate fraction contains alkaloids, steroids, flavonoids and phenolics. The remaining ethanol fraction contains alkaloids, triterpenoids, flavonoids and phenolics. Keywords: Allamanda Catharica L. (Alamanda), Secondary Metabolites, Fractionation